2021
DOI: 10.3389/fmicb.2021.666689
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Analysis of Bacterial Isolates From Necrotic Wheat Leaf Lesions Caused by Xanthomonas translucens, and Description of Three Putative Novel Species, Sphingomonas albertensis sp. nov., Pseudomonas triticumensis sp. nov. and Pseudomonas foliumensis sp. nov.

Abstract: Xanthomonas translucens is the etiological agent of the wheat bacterial leaf streak (BLS) disease. The isolation of this pathogen is usually based on the Wilbrink’s-boric acid–cephalexin semi-selective medium which eliminates 90% of other bacteria, some of which might be novel species. In our study, a general purpose nutrient agar was used to isolate 49 bacterial strains including X. translucens from necrotic wheat leaf tissues. Maximum likelihood cluster analysis of 16S rRNA sequences grouped the strains into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 101 publications
(159 reference statements)
1
12
0
Order By: Relevance
“…S3). The results of isoprenoid quinone analysis indicated that the major quinone of LJ2 T was Q-9 (89.06 %), which is consistent with those of other species of the genus Pseudomonas [21,30,31], ubiquinone Q-8 (10.94 %) was also detected.…”
Section: Physiology and Chemotaxonomysupporting
confidence: 76%
“…S3). The results of isoprenoid quinone analysis indicated that the major quinone of LJ2 T was Q-9 (89.06 %), which is consistent with those of other species of the genus Pseudomonas [21,30,31], ubiquinone Q-8 (10.94 %) was also detected.…”
Section: Physiology and Chemotaxonomysupporting
confidence: 76%
“…The most recent and valid nomenclature for this pathogen is X. translucens p v. undulosa (Smith et al) Vauterin, Hoste, Kersters and Swings 1995. Xtu is reported to infect both wheat and barley while Xtt is pathogenic to only barley [8,28]. The complete current taxonomy of Xtu is Kingdom Bacteria; Phylum Proteobacteria; Class Gammaproteobacteria; Order Xanthomonadales; Family Xanthomonadaceae; Genus Xanthomonas; and Species X. translucens.…”
Section: Taxonomymentioning
confidence: 99%
“…Generally, a leaf sample with young BLS lesions is selected, thoroughly washed in running water, surface disinfected, and blotted dry. About 0.25 cm 2 sections of symptomatic leaf tissue are aseptically excised, bisecting, at least, one lesion and immersed in a 100 μl droplet of sterile water, and incubated at room temperature for 5 min [28]. Using a 10-μl loop, the suspensions are streaked onto appropriate non-selective culture media e.g.…”
Section: Isolation and Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the seed infection process, how black chaff develops or if seed infection is the main mechanism of Xtt dispersal. Xtt is increasingly impactful to cereal growers worldwide with recent widespread reports in the northern United States (Curland et al 2020), Iran (Habibian et al 2021) and Canada (Tambong et al 2021). Though losses in barley due specifically to Xtt have not been quantified, wheat farmers can experience yield reduction as high as 40% due to infection with the closely related pathogen X. translucens pv.…”
mentioning
confidence: 99%